Economic Effect of Hybrid Catfish (Channel Catfish ♀ × Blue Catfish ♂) Growth Variability on Traditional and Intensive Production Systems. (30th August 2021) - Gosh, Kamal; Hanson, Terry R.; Drescher, David; Robinson, Dalton; Bugg, William; Chatakondi, Nagaraj; Kumar, Ganesh; Jeffers, Carl; Dunham, Rex A.
Abstract: Using hybrid catfish (Channel Catfish Ictalurus punctatus ♀ × Blue Catfish I. furcatus ♂ ) is one path toward intensification that can lower production costs and increase net returns. However, hybrid catfish have experienced growth variability resulting in undersized and oversized fish. Analyzing the economic effect of this issue is critical, as fish processors often require a specific size range of fish from the producers. Comparative economic analyses were performed using enterprise budgets and sensitivity analyses on hybrid catfish production data obtained from single‐batch (SB), multiple‐batch (MB), and split‐pond (SP) systems. Results indicated that the SP system had the highest net returns (US$8, 164/ha) resulting from greater availability of premium‐sized fish (0.45–1.81 kg; sales price = $2.46/kg), followed by SB and MB systems, respectively. Lower prices received for undersized (<0.45 kg; sales price = $2.34/kg) and oversized (>1.81 kg; sales price = $2.08/kg) fish resulted in revenue losses of $287, $594, and $611 per hectare in SB, MB, and SP systems, respectively. An inverse relationship between the dockage rate and net returns was observed. Economic analyses also showed that the net returns were greater when large‐sized fingerlings (~20 cm) were stocked relative to medium‐sized fingerlings (≤18 cm) in the SP and SB systems, while the opposite was true for the MB system. Stocking of graded hybrids in SB, MB, and SP production could provide higher net returns from these systems.